Tafsir Iqtisadi di Indonesia: Metodologi, Validitas dan Kontribusi - Baharuddin, Didin (Proceedings of International Conference on Muslim Society and Thought, 2024)
Abstract: This research aims to examine the works of Tafsir Iqtisadi/Tafsir on economic verses published in Indonesia from 2012 to 2023. Many of these works appeared when Sharia economics was developing, especially when PTKI opened a Sharia Economics Department in Indonesia. Have we employed the descriptive-analytical method, and historical philosophical approach, and based on the literature study, this article finds that Tafsir Iqtisadi in Indonesia is a tafsir product, which is a book and research in itself. The Tafsir Iqtisadi product is an interpretation of the Al-Quran with an economic approach. This approach is an acceptable style of interpretation and originates from the style of Tafsir Ilmi, Tafsir Ahkam and Tafsir Adabi Ijtima’i. Methodologically, the Tafsir Iqtisadi books combine tafsir bil ra’yi and tafsir bil ma’tsur. Meanwhile, the presentation of Tafsir Iqtisadi products consists of the presentation of tahlili, ijmali and maudhui. In terms of validity, Tafsir Iqtisadi can be said to be valid because it is in accordance with general interpretation methods, and also become a theological and conceptual foundation tool in developing Sharia Economics in Indonesia.